2021
DOI: 10.1155/2021/9989756
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr Virus Mucocutaneous Ulcer: An Unexpected Diagnosis of a New Entity

Abstract: Epstein–Barr virus mucocutaneous ulcer (EBVMCU) is a new entity, only recently included in World Health Organisation classification of lymphoid neoplasms. Almost all cases described to date have been in patients with a predisposing risk factor of immunosuppression. This case presents a 21-year-old male admitted with tonsillitis and no overt immunosuppression, who is subsequently diagnosed with EBVMCU of likely iatrogenic origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Howden et al . suggested that EBV‐positive DLBCL was usually associated with mass lesions and only large cells in DLBCL were EBER‐positive, whereas cells of various sizes in EBVMCU were EBER‐positive 10 . It should be noted that immunoglobin heavy chain gene rearrangement alone does not prove to be neoplastic 2,8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Howden et al . suggested that EBV‐positive DLBCL was usually associated with mass lesions and only large cells in DLBCL were EBER‐positive, whereas cells of various sizes in EBVMCU were EBER‐positive 10 . It should be noted that immunoglobin heavy chain gene rearrangement alone does not prove to be neoplastic 2,8 .…”
Section: Discussionmentioning
confidence: 99%
“…9 Howden et al suggested that EBV-positive DLBCL was usually associated with mass lesions and only large cells in DLBCL were EBER-positive, whereas cells of various sizes in EBVMCU were EBER-positive. 10 It should be noted that immunoglobin heavy chain gene rearrangement alone does not prove to be neoplastic. 2,8 Since there are no established diagnostic criteria based only on the morphopathological features of EBVMCU, the clinical presentation (e.g., medical history, gross findings, location, and absence of mass lesions) is very important.…”
Section: Ebvmcu Cases Although Discrepancies Between Studies Dependingmentioning
confidence: 99%